Use of aminothiophenol as an indicator for the analysis of silver nanoparticles in consumer products by surface-enhanced Raman spectroscopy. Issue 18 (28th June 2016) - Nguyen, Trang H. D.; Zhou, Peng; Mustapha, Azlin; Lin, Mengshi
Abstract : Silver nanoparticles (Ag NPs) are one of the top five engineered nanoparticles that have been used in various products. Abstract : Silver nanoparticles (Ag NPs) are one of the top five engineered nanoparticles that have been used in various products. Current methods for the measurement of Ag NPs are time consuming and expensive. Therefore, it is of critical importance to develop novel strategies to detect the presence of Ag NPs at low concentrations in different matrices. This study aimed at detecting and measuring Ag NPs in consumer products using surface-enhanced Raman spectroscopy (SERS) coupled with aminothiophenol (PATP) as an indicator molecule that binds strongly with Ag NPs. Quantification and qualification of Ag NPs were achieved using this method of acquiring SERS signals from Ag NP–PATP complexes. Four dietary supplement products and one nasal spray were selected to evaluate the performance of SERS in the detection of Ag NPs. Inductively coupled plasma optical emission spectrometry (ICP-OES) and transmission electron microscopy (TEM) were utilized to measure the physical properties of Ag NPs in the samples. The results demonstrate that distinctive Raman peaks of PATP can be used to distinguish Ag NPs from silver bulk particles and silver nitrate. SERS is able to detect Ag NPs with different sizes ranging from 20 to 100 nm, with the highest intensity for ∼30 nm Ag NPs. A partial least squares method was used to develop quantitative models for the analysis of spectral data ( R = 0.94). These results indicate that the conjugation of Ag NPs with PATP can be measured by SERS. These results demonstrate that SERS is a simple and rapid method and has great potential to detect Ag NPs in various products.